The Triage Effectiveness of an Extended High-Risk Human Papillomavirus Genotyping Assay for Women with Cytology Showing Atypical Squamous Cells of Undetermined Significance in China - Pan D; Dong B; Gao H; Mao X; Xue H; Sun P (Dove Medical Press, 2020)
Diling Pan1 ,* Binhua Dong2,3 ,* Hangjing Gao,2 Xiaodan Mao,2,3 Huifeng Xue,4 Pengming Sun2,3 1Department of Pathology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou 350001, Fujian, People’s Republic of China; 2Department of Gynecology, Laboratory of Gynecologic Oncology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian 350001, People’s Republic of China; 3Fujian Key Laboratory of Women and Children’s Critical Diseases Research, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian 350001, People’s Republic of China; 4Fujian Provincial Cervical Disease Diagnosis and Treatment Health Center, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou 350001, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengming SunFujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, 18 Daoshan Road, Fuzhou 350001, Fujian, People’s Republic of ChinaTel +86-591-87558732Fax +86-591-87551247Email sunfemy@hotmail.comPurpose: Little is known about the performance of extended high-risk human papillomavirus (HR-HPV) genotyping triage of cytology showing atypical squamous cells of undetermined significance (ASC-US). This study aims to evaluate the effectiveness of triage with different HR-HPV genotype models among women with ASC-US.Materials and Methods: In this study, all women who underwent cervical cytology and HR-HPV genotyping were enrolled from 2014 to 2017 in China, and those with cytology showing ASC-US were referred for colposcopy and/or biopsy. The endpoint was histological detection of cervical intraepithelial neoplasia grade 2 or worse (CIN2+). The outcome indicators were the sensitivity, specificity, positive predictive values (PPVs), negative predictive values (NPVs) and colposcopy referral rates.Results: In all, 56,788 women were enrolled in this study, and 2658 (4.97%) women were reported to have ASC-US; 10.1% (242/2393) of women with ASC-US were identified as having CIN2+. The HR-HPV infection rate was 95.0% among all women with ASC-US who were identified as CIN2+, and the top five genotypes with prevalence and risk of CIN2+ were HPV16 (OR=26.38), HPV58 (OR=7.04), HPV18 (OR=4.44), HPV33 (OR=3.38), HPV31 (OR=2.97) and HPV52 (OR=2.96). The HPV16/18/31/33/52/58 model achieved higher sensitivity [91.3 (87.8– 94.9)], specificity [70.0 (68.1– 72.0)], PPV [25.5 (22.4– 28.2)] and NPV [98.6 (97.3– 98.7)] for the triage of ASC-US patients than the other HR-HPV-type combination models, but the colposcopy referral rate (36.2%) was significantly lower than that of the recommended HR-HPV nongenotyping model (47.6%).Conclusion: This study confirms that the specific HR-HPV genotype HPV16/18/31/33/52/58 is an alternative strategy for ASC-US triage and can effectively reduce the high burden of colposcopy referrals in China.Keywords: human papillomavirus, genotyping, atypical squamous cells of undetermined significance, cervical intraepithelial neoplasia